Measurement of Blood Pressure in Children : A Systematic Approach (Journal of Chittagong Medical College Teachers' Association, 2012)
Measurement of blood pressure properly is important. Prevalence of hypertension in children is not less. Morbidity and mortality of hypertension cannot be ignored. Blood pressure (BP) should be measured systematically among children over 3 years old who are seen in a medical setting. Among